2008
DOI: 10.1093/humupd/dmn053
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of the retrieval of a low number of oocytes following mild ovarian stimulation for IVF: a meta-analysis

Abstract: The optimal number of retrieved oocytes depends on the ovarian stimulation regimen. After mild ovarian stimulation, a modest number of oocytes is associated with optimal implantation rates and does not reflect a poor ovarian response. Therefore, the fear of reducing the number of oocytes retrieved following mild ovarian stimulation appears to be unjustified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
2
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(134 citation statements)
references
References 45 publications
7
119
2
6
Order By: Relevance
“…This observation agrees with previous studies that reported that the outcome of IVF treatment is not affected by the use of a "mild" stimulation if at least five oocytes are obtained at follicular aspiration [22,23]. Since both stimulation strategies allowed to obtain a similar number of mature oocytes, even the proportion of cycles in which spare embryos and oocytes were available for freezing was similar.…”
Section: Discussionsupporting
confidence: 91%
“…This observation agrees with previous studies that reported that the outcome of IVF treatment is not affected by the use of a "mild" stimulation if at least five oocytes are obtained at follicular aspiration [22,23]. Since both stimulation strategies allowed to obtain a similar number of mature oocytes, even the proportion of cycles in which spare embryos and oocytes were available for freezing was similar.…”
Section: Discussionsupporting
confidence: 91%
“…Five retrieved oocytes were associated with an ideal ongoing pregnancy rate (67 %) per embryo transfer in patients undergoing a mild stimulation protocol using GnRH-antagonist [49,50]. On the other hand, a development of less than five follicles in a standard stimulation protocol is usually associated with poor outcome related to the low number transferred embryos and high cancellation rate due to the fertilization failure [51].…”
Section: Discussionmentioning
confidence: 99%
“…The optimal number of retrieved oocytes depends on the ovarian stimulation regimen (22) . However, age and season both significantly affect the response of oocyte developmental competence to FSH stimulation (23) .…”
Section: Results:-effect Of Xenotransplantation Techniques On Number mentioning
confidence: 99%